Morphometric Plasticity of Nitric Oxide Containing Neurons in the Barrel Cortex of De-whiskered Rats - Afarinesh, Mohammad Reza; Behzadi, Gila (Novelty in Biomedicine, 2015)
Background: The rodent somatosensory barrel cortex is an ideal model to examine the effect of experience-dependent plasticity on developing brain circuitry. Sensory deprivation such as whisker deprivation may affect neuroanatomical aspects of the brain during developmental processes. The present study designed to investigate the possible effects of whisker deprivation on the morphometric characteristics of NADPH-d positive neurons in the barrel field cortex of adolescent rats. Materials and Methods: Pups were divided into the intact (n=4) and whisker-deprived groups (n=4). In whisker-deprived group, the total whiskers of subjects were trimmed every other day from postnatal day (PND) 0 to PND 60. NADPH-d histochemistry reaction was processed to quantitatively analyze the feature of NADPH-d containing neurons of barrel cortex. Results: Our results showed that the number of NADPH-d positive neurons remained unchanged in whisker-deprived group compared to controls. The mean soma diameter, dendritic length and the number of 3rd order processes were significantly decreased in the whisker-deprived rats (p<0.05). Conclusion: Our results indicate that postnatal whisker deprivation possibly alter NADPH-d/NOS neuronal features in the barrel cortex. The functional implications of these data may relate the plasticity of synaptic receptive field and developmental brain circuits.